Jaboulay gastroduodenostomy for pyloric obstruction after corrosive ingestion - Supangat; Muhammad Yuda Nugraha; Peter Lundqvist (Elsevier, 2020)
Strong acid accidental ingestion is a common case in rural society and children. The effect of strong acids may cause injuries of the gastrointestinal tract. We present a case obstruction in the distal part of gastric after accidental sulfuric acid ingestion in children. Sulfuric acid ingestion is potential in children since its commercial product physical appearance looks like drink water. Then the patient was diagnosed with pyloric obstruction after barium meal examination and was treated using Jaboulay gastroduodenostomy procedure.